2023
DOI: 10.1002/qj.4525
|View full text |Cite
|
Sign up to set email alerts
|

Subselection of seasonal ensemble precipitation predictions for East Africa

Abstract: The Greater Horn of Africa (GHA) is highly vulnerable to climate and weather hazards such as drought, heat waves, and floods. There is a need for accurate seasonal forecasts to prepare for risks (such as crop failure and reduced grazing opportunities) and take advantage of favorable conditions (rains arrive on time and where they are needed) when they arise. As such, information at finer spatial scales than current state‐of‐the‐art global prediction models can provide is needed. Dynamical downscaling is one me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…With the increase in ensemble members from Global Climate Centers and the need to run high resolution models, there is need for methods of selecting ensemble members. Heinrich-Mertsching et al (2023b) showed that sub-selection of ensemble members leads to systematically higher skill than random sub-selection.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…With the increase in ensemble members from Global Climate Centers and the need to run high resolution models, there is need for methods of selecting ensemble members. Heinrich-Mertsching et al (2023b) showed that sub-selection of ensemble members leads to systematically higher skill than random sub-selection.…”
Section: Figurementioning
confidence: 99%
“…To tackle this issue, further research needs to be conducted to enhance the accuracy of Long rains forecasts. This could involve the integration of new statistical approaches, ensemble member selection (Heinrich-Mertsching et al, 2023b), ongoing research on exploring the utilization of machine learning techniques (Deman et al, 2022) and hybrid methods that take into consideration the different forecasting approaches.…”
Section: Research Modeling and Predictionmentioning
confidence: 99%
See 1 more Smart Citation